Earthquake Disaster Mitigation Explanation to Prepare a Disaster Response Generation for Students in 3th-Grade of Elementary School - Ilham Nurfalah; Rina Maryanti; Verra Wulandary; Asep Rudi Irawan (ASEAN Journal of Science and Engineering Education, 2022)
Empowerment of children aged from early to understand the mitigation of disasters is a step early build community aware of disaster so that when it happens a disaster then participants Extension is that teachers and children ages early in Community learning activity centre Baitul Muttaqin that is in place is no longer confusion and panic because it has understood how to how to overcome and reduce the risk of disaster. The purpose of knowledge that is acquired during the extension quake earth is transmitted to the environment around in order to reduce the risk of disaster, then the method of observation participant and pre-test post-test used in the extension of this. Results achievement and conclusions in the activity is as follows: a) Have their knowledge and understanding of the mitigation of disaster so that every action aims to increase self-awareness them about the disaster that potentially occur, and b) it has knowledge of preparedness will mitigate the disaster which aims to tackle and reduce the impact of disasters or long - term risks to property and human life.